Women in graphic design 1890-2012 = Frauen und Grafik-Design - Breuer, Gerda, 1948-; Meer, Julia, 1982- (Jovis, 2012)
"Why do apparently so few women feature in the history of design? Why is it still the case that so few women speak at conferences? Why are previously well-known women "forgotten"? What effects does the gender debate have on today's everyday working life? Are women judged today solely on the basis of their quality of work? Since professionalization began, female graphic designers have been working actively and successfully, but the artificial synthesis of masculinity and artistic genius has repeatedly prevented women-with few exceptions-to be recognised in "official" design history. Still today, despite the claim that the gender issue is obsolete in graphic design, only a tiny percentage of active female designers enjoy public acclaim. This opulently illustrated volume finally sets out to fill this gap. It presents the most significant female designers and portrays their paths to professionalization, with numerous short biographies alongside essays, sources and detailed discussions."-- Vydavatelská anotace
Životopisné údaje
Keywords: studie; studies; 19.-21. století; 1890-2012; grafický design -- 19.-21. století; designérky -- 19.-21. století; graphic design -- 19th-21st centuries; women designers -- 19th-21st centuries